2020
DOI: 10.3390/ma13112493
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Layer Directions on the Properties of 316L Stainless Steel Parts Fabricated through Fused Deposition of Metals

Abstract: Metal specimens were fabricated via the fused deposition of metals (FDMet) technique with a filament composed of the 316L stainless steel particles and an organic binder. This process was adopted due to its potential as a low-cost additive manufacturing process. The objective of this study is to investigate the influence of the processing conditions—layer directions and layer thicknesses—on the mechanical and shrinkage properties of the metal components. The specimens were printed in three different layer dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 21 publications
(27 reference statements)
5
84
0
Order By: Relevance
“…The anisotropic behavior is controlled by the effect of gravity on the metal part during the sintering process. Kurose et al [8] reported linear shrinkage values which varied with the building orientation between 14% and 23%. Gong et al [9] reported similar shrinkage values but they also noted that features at a lower height shrank less than the same feature at a higher height.…”
Section: Sintered Parts 321 Dimensional Analysis Of the Sintered Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The anisotropic behavior is controlled by the effect of gravity on the metal part during the sintering process. Kurose et al [8] reported linear shrinkage values which varied with the building orientation between 14% and 23%. Gong et al [9] reported similar shrinkage values but they also noted that features at a lower height shrank less than the same feature at a higher height.…”
Section: Sintered Parts 321 Dimensional Analysis Of the Sintered Pmentioning
confidence: 99%
“…Kurose et al [8] studied the effects of different building orientations for 316L printed parts using their own filament. All the parts were printed with a rectilinear infill pattern and at 100% infill density varying the layer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…In FFF and the other MEX techniques [ 8 , 14 , 31 , 32 , 33 , 34 , 35 , 36 ], the generation of the shape by the extrusion of material strands, known as roads, can result in defects in the gaps between the strands or weak areas if the bonding between the strands is not sufficient [ 8 ]. In early investigations, different solutions were proposed to reduce these defects [ 8 , 10 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows the dimensional shrinkage values of the as-sintered and as-aged specimens. Anisotropic shrinkage after sintering has been reported in previous studies of FDMet-fabricated parts [ 23 , 24 , 25 ]. The binder domains were oriented perpendicular to the layer direction and were both thin and thick in the green parts.…”
Section: Resultsmentioning
confidence: 60%
“…The filaments were input to a modified commercial FDM 3D printer (L-DEVO M2030TP, Fusion Technology Co., Tokyo, Japan) [ 23 ]. Because the produced filament was too brittle for printing at room temperature, a temperature-controlled chamber for the filament was prepared, and a flexible duct was connected from the chamber to the extruder unit of the 3D printer.…”
Section: Methodsmentioning
confidence: 99%